ChemInform Abstract: Preparation, Electronic Structure and Luminescence Properties of Ce3+‐Activated CaZnOS under UV and X‐Ray Excitation. Issue 18 (17th April 2014) - Zhang, Zhi‐Jun; Feng, Ang; Sun, Xin‐Yuan; Guo, Kai; Man, Zhen‐Yong; Zhao, Jing‐Tai
Abstract: Ca1‐2x Cex Lix ZnOS samples (0 ≤ x ≤ 0.15) are prepared by a solid‐state reaction of CaO, ZnS, Li2 CO3, and CeO2 (5% H2 /N2 reducing atmosphere, Mo crucible, 950—1050 °C, 48 h).